Identification of antigen-specific B-cell receptor sequences from the total B-cell repertoire - Galson, J; Kelly, D; Trück, J (Begell House, 2016)
Advances in next-generation sequencing now allow characterization of the global B-cell receptor (BCR) heavy-chain repertoire at a level that reflects its huge diversity. This technology has provided great insight into the structure of the BCR repertoire and how it responds to specific antigen stimuli. There are numerous potential clinical and research applications of BCR repertoire sequencing, but a major hurdle in the realization of these applications is the identification of the antigen-specific sequences of interest from within the total repertoire. To deconvolute the antigen-specific sequences from total repertoire, either a source of antigen-enriched sequence data is required with which to annotate the total repertoire, or de novo annotation methods must be used based on preconceptions of the features of antigen-specific sequences and their behavior following antigen-specific immune stimulation. We present a review of how these different methods can be applied to identify antigen-specific BCR sequences from the total BCR repertoire.